PENGARUH PEMBERIAN TERAPI BEKAM TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI KLINIK BEKAM SEHAT Dr. ABDURRAHMAN PASAR 1 TANJUNG SARI MEDAN SELAYANG TAHUN 2021 - Tinah Tinah; Cecep Triwibowo; Harijun (Poltekkes Kemenkes Medan, 2022)
Hypertension is one of the most common diseases in Indonesia and is the third leading cause of death for all ages (7.4%). Hypertension is defined as blood pressure that exceeds 140/90 mmHg. Management of hypertension can be done with pharmacological, non-pharmacological, tertiary and complementary approaches. One of the complementary therapies used is cupping. Cupping is a cleansing method by removing blood and wind from the body through the surface of the skin by sucking. This study aims to determine the effect of cupping therapy on reducing blood pressure in patients with hypertension. The design of this study was a clinical trial with a one group pretest-posttest design. The number of samples was 30 respondents according to the inclusion criteria, namely hypertension sufferers by performing 1 intervention before and after cupping therapy. The results of statistical tests found that there was a change in blood pressure, namely a decrease with the difference in the mean values ??of systole (4.851) and diastole (4.427). The statistical test used is the Wilcoxon test on systole and diastole showing a value (p = 0.000) which means p value <0.05 so H1 is accepted which means that there is a significant effect of cupping therapy on reducing blood pressure in hypertensive patients at the Health Cupping Clinic dr. Abdurrahman Medan. The researcher's suggestion for future researchers is to examine the effects of long-term cupping therapy.